Esterilização não - cirúrgica com quinacrina em mulheres infectadas pelo vírus da imunodeficiência humana - HIV - Deborah Randazzo Barbosa de Magalhaes (2007)
The objective of this study was to evaluate the safety of the nonsurgicalQuinacrine sterilization (QS) method for HIV-infected women using the clinical assessment of short time adverse events, analysis of viral load, CD4+ and CD8+ lymphocytes counting and transvaginal ultrasonography. This open trial study included 64 HIV-infected women and 194 anti-HIV negative women requesting sterilization and was carried out from February 2005 to August 2006 at the Family Planning Clinic, School of Medicine of the Federal University of Minas Gerais, Belo Horizonte, Brazil. Three doses of 252 mg/month of Quinacrine, in pellets, were inserted transcervically in the uterine fundus during the follicular phase of themenstrual cycle. Adverse events related to QS were light abdominal cramping, vulvar itching and uterine bleeding. Uterine bleeding was the only short term side effect more frequent in HIV-infected women. No serious adverse events occurred in any of the two groups. The viral load, the CD4+ and CD8+ counting did not show any significant variation after the QS. There was not any significant difference concerning the occurrence of hyperecogenic spots in the uterine fundus in the two groups. The average follow-up time was 10.36 months. The cumulatedsurvival rate in the Lifetime Table was 0.9875 (SE 0.0089), 95% CI (0.970-1.000). The Pearl index was 0.8753 per 100 women/year. Quinacrine was considered a safe drug for the sterilization of HIV-infected women.